Real World Evidence of User Experience with Microenemas for Relief of Constipation - Stefanie Rasche; Christer Spegel; Katarina Lundh (Drugs - Real World Outcomes)
Abstract Background Constipation is a commonly reported gastrointestinal complaint. Research on this widespread condition focuses mainly on clinical trials for chronic constipation with less emphasis on patient experience and nonchronic situations. Sufferers report that constipation interferes with daily activities and quality of life. It is likely that this is common among all sufferers of constipation, regardless of how often the condition is experienced. Objective This work explored attitudes and perceptions of people who experience occasional constipation and self-treat with over the counter products, particularly Microlax® microenemas. Methods In this retrospective study, real-world data were collected from 1635 respondents from France and Russia who experienced occasional constipation. Participants completed a questionnaire about their experiences with occasional (not chronic) constipation and perceptions of over the counter treatments of oral laxatives, suppositories, and Microlax microenemas. Questions focused on comfort, quality of life, ease of use, and reliability of these treatments. Participants had used the microenema for treatment of occasional constipation within 3 months of study participation. Occasional constipation was based on the Rome IV diagnostic criteria for adults and babies. Data were analyzed across the total population of all groups, then by subgroup. Success criteria were defined as of at least 70% agreement with the statements scoring ≥ 7 on the scale of 0–10. The proportion of respondents agreeing with the individual statements was calculated using the denominator for the total sample within each group. Results This study shows that experiencing even occasional bouts of constipation negatively affect quality of life and well-being. Participants (women aged 25–54 years, older men, and women aged 60–80 years) reported that it severely limited daily life and activities and caused negative emotions and embarrassment. Pregnant women and mothers with babies showed great concern that constipation indicated a serious and painful condition and was bad for their babies. Participants agreed that using Microlax microenema provided greater ease of use, comfort, reliability, and safety than oral laxatives and rectal suppositories. Conclusions Sufferers of occasional constipation report that these bouts interfere with their daily lives and reduce quality of life, similar to what is reported for those with chronic constipation based on existing literature. The microenema, Microlax, showed benefits in the relief of occasional constipation compared with oral laxatives and rectal suppositories. Trepidation about using the microenema, experienced before using it, was greatly reduced after the first and subsequent uses. Microlax microenema enabled users to regain the feeling of control and provided positive impacts on quality of life and well-being.